Interaction of the Left Dorsolateral Prefrontal Cortex (l-DLPFC) and Right Orbitofrontal Cortex (OFC) in Hot and Cold Executive Functions: Evidence from Transcranial Direct Current Stimulation (tDCS) - Nejati, Vahid; Salehinejad, Mohammad Ali; Nitsche, Michael A. (Neuroscience, 2018)
•Cold EF rely on Central-Executive Network, specifically left DLPFC activation.•Hot EF rely on Default Mode Network and central-executive network, benefitting from both left DLPFC and right OFC activation.•Inhibitory control and risk taking are the coldest and hottest EF domains respectively.•EF are on a continuum with cold and hot domains related to lateral and mesial prefrontal areas.•None of EF domains are purely cold or purely hot. An organizing principle which has recently emerged proposes that executive functions (EF) can be divided into cognitive (cold) and affective/reward-related (hot) processes related to the dorsolateral prefrontal cortex (DLPFC) and orbitofrontal cortex (OFC) respectively. A controversial question is whether cold and hot EF are functionally and structurally independent or not. This study investigated how the left DLPFC (l-DLPFC) and right OFC (r-OFC) interact in hot and cold EF using transcranial direct current stimulation (tDCS). Twenty-four healthy male subjects received anodal, cathodal and sham tDCS (20 min, 1.5 mA) over the l-DLPFC (F3) and r-OFC (Fp2) with a 72-h interval between each stimulation condition. After five minutes of stimulation, participants underwent a series of cold and hot EF tasks including the Go/No-Go and Tower of Hanoi (TOH) as measures of cold EF and the BART and temporal discounting tasks as measures of hot EF. Inhibitory control mostly benefited from anodal l-DLPFC/cathodal r-OFC tDCS. Planning and problem solving were more prominently affected by anodal l-DLPFC/cathodal r-OFC stimulation, although the reversed electrode position with the anode positioned over the r-OFC also affected some aspects of task performance. Risk-taking behavior and risky decision-making decreased under both anodal l-DLPFC/cathodal r-OFC and anodal r-OFC/cathodal l-DLPFC tDCS. Cold EF rely on DLPFC activation while hot EF rely on both, DLPFC and OFC activation. Results suggest that EF are placed on continuum with lateral and mesial prefrontal areas contributing to cold and hot aspects respectively.